Brazilian scientific production on the Impact Factor indicator: a study at the SciELO, Scopus and Web of Science bases - Almeida, Catia Candida de [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Univ Federal Santa Catarina, 2019)
This research analyzes the Brazilian scientific papers published in journals indexed in SciELO, Scopus and Web of Science databases that approach the indicator Impact Factor (IF), as a methodological procedure or object of study. Brazilian papers with the term fator de impacto or impact factor were searched from 2005 to 2015. The co-word analysis was used to identify the correlations between keywords and the term IF. As result, it was possible identify the knowledge area and the subject dealt, allowing to understand the approaching ways this indicator in Brazilian research.
Keywords: Information Science; Bibliometrics; Impact factor; Database